Simply the best [large type] - Phillips, Susan Elizabeth (Phillips, Susan Elizabeth. Chicago Stars novel., 2024)
When Brett, the hottest sports agent in the business, and Rory, the sister of his superstar client, meet and have a disastrous one-night stand, resulting in murder, they find things getting messy, dangerous, heartbreaking and sexy as they struggle with themselves, each other and love.